MODEL PEMBELAJARAN KOOPERATIF ING NGARSA SUNG TULADHA - Hutagaol, Kartini; Saija, Louise M.; Simanjuntak, Debora C. C. (LPPM Universitas Advent Indonesia, 2018)
Today it is often seen on television shows that moral damage to national graduatesis very worrying, acts of corruption (bribery cases), juvenile delinquency, brawls betweenstudents with physical violence, brutal suicide bombings, and anarchists. In responding to thereality of the moral crisis, the alarming character crisis faced by the Indonesian Nation, the2013 Curriculum has emphasized and directed the nature of education to improve attitudes,which is the essence of education in the real context, as also believed by Ki Hadjar Dewantara,MODEL PEMBELAJARAN KOOPERATIF ING NGARSA SUNG TULADHAKartini Hutagaol1, Louise M. Saija2, Debora C. Simanjuntak390regarding the effort in debriefing the national spirit , the spirit of brotherhood, protecting thosewho apply values that exemplify manners, to form moral people, who have a mind set (tocommit) that is in harmony with social values. The author team conducted a cooperativelearning model design that inspired the idea of Ki Hadjar Dewantara, as revealed by Soedjadi